2015
DOI: 10.1007/s11356-015-4867-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ecotoxicity and chemical approaches to compare the effects of ZnO nanoparticles, ZnO bulk, and ZnCl2 on plants and microorganisms in a natural soil

Abstract: This work compared the toxicity of ZnO nanoparticles (ZnO-NPs), ZnO bulk, and ZnCl2 on microbial activity (C and N transformations and dehydrogenase and phosphatase activities) and their uptake and toxic effects (emergence, root elongation, and shoot growth) on three plant species namely wheat, radish, and vetch in a natural soil at 1000 mg Zn kg(-1). Additionally, plants were also tested at 250 mg Zn kg(-1). The effects of the chemical species on Zn extractability in soil were studied by performing single and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Zn partitioning is inextricably linked to soil acidity (Sauvé et al 2000), which, in turn, depends on the form of Zn added to the soil. In this study, a relatively low pH was observed for ionic treatments, and a relatively high pH was observed for NP treatments, which is consistent with the results of other studies (Kool et al 2011; Garcia-Gomez et al 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Zn partitioning is inextricably linked to soil acidity (Sauvé et al 2000), which, in turn, depends on the form of Zn added to the soil. In this study, a relatively low pH was observed for ionic treatments, and a relatively high pH was observed for NP treatments, which is consistent with the results of other studies (Kool et al 2011; Garcia-Gomez et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…It has been already recognized that upon reaching the soil, ZnO-NPs may have a negative impact on soil microorganisms, invertebrates, and plants (Hou et al 2018). Most studies have found, however, that ZnO-NPs are less toxic than zinc ions to soil-dwelling organisms (Garcia-Gomez et al 2015), including earthworms (Kwak and An 2015). Initially, the dissolution of zinc ions rather than the direct impact of NPs was proposed as the mechanism underlying the toxicity of ZnO-NPs (Kool et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, interaction with silver ions (0.1 mM–1 mM) changed the biochemical, physiological and morphometric parameters, such as distorting the root epidermal structure or altering the anatomical features of sunflower plants [44]. ZnONPs (1000 mg/L) and copperNPs (500 mg/L) have also been demonstrated to slow the growth of seedlings [45,46]. In this type of study, an evaluation of the direct and indirect effects on the plants should be based on different nanomaterials and various plant species [4].…”
Section: Resultsmentioning
confidence: 99%
“…To better examine the phytotoxicity effect of soil contaminated by NPs, we have chosen to grow the soybean plants in soil with TiO 2 and Fe 3 O 4 NPs treatments that were applied as water suspension to mimic the condition of soil contamination by NP run offs. Such an application method has been commonly used in previous soil-based plant studies and has provided sufficient exposure and bioavailability of the NPs to the plants [ 7 , 23 , 24 ]. We found that TiO 2 NPs significantly reduced plant growth as compared to Fe 3 O 4 and these changes were also accompanied by reductions in leaf C content.…”
Section: Resultsmentioning
confidence: 99%